P6.2 AORTIC-TO-BRACHIAL STIFFNESS GRADIENT INDEPENDENTLY PREDICTS KIDNEY FUNCTION: CASE-CONTROL COMPARISON BETWEEN PATIENTS WITH TYPE 2 DIABETES AND NON-DIABETIC CONTROLS - Dean Picone*; Martin Schultz; Rachel Climie; Velandai Srikanth; James Sharman (Artery Research, 2015)
Background: A negative aortic-brachial stiffness gradient (ab-SG), whereby aortic pulse wave velocity (aPWV)≥brachial PWV (bPWV) predicts mortality independent of aPWV in dialysis patients. Patients with type 2 diabetes mellitus (T2DM) have increased risk of renal damage and exhibit haemodynamic abnormalities that may alter ab-SG. This study aimed to determine if there were differences in ab-SG among patients with T2DM compared with non-diabetic controls, and also to determine associations between ab-SG, aPWV and kidney function. Methods: 60 patients with T2DM and 60 age- and sex-matched non-diabetic controls (58±8 years, 55% male both) had ab-SG measured by applanation tonometry, with ab-SG defined as the quotient of bPWV (carotid-to-radial) and aPWV (carotid-to-femoral). Kidney function was assessed by estimated glomerular filtration rate (eGFR). Results: ab-SG was significantly lower in patients with T2DM (0.99±0.2 versus 1.2±0.3, p<0.001) and aPWV, but not bPWV, was significantly higher (p<0.001, p=0.25). 58% of patients with T2DM versus 27% of non-diabetic controls (χ2=11.0, p<0.001) had negative ab-SG (aPWV≥bPWV). ab-SG predicted eGFR in the entire cohort independent of age, sex, T2DM status and cardiovascular risk factors (β=17.0, p=0.005), whereas aPWV was a weaker correlate of eGFR (β=−0.15, p=0.22). Independent predictors of ab-SG were brachial and central pulse pressure (β=−0.008, p=0.005; β=−0.007, p=0.027) for patients with T2DM and heart rate (β=−0.012, p=0.007) and brachial pulse pressure (β=−0.012, p=0.026) for non-diabetic controls. Conclusions: Patients with T2DM have reduced (negative) ab-SG. In the entire cohort, ab-SG predicted kidney function independent of aPWV, implying that negative ab-SG may have a pathophysiological function.